Psychometric properties of the person-centred coordinated care experience questionnaire (P3CEQ) in a Norwegian radiotherapy setting. (25th August 2022) - Sollid, May ingvild volungholen; Slaaen, Marit; Danielsen, Signe; Kirkevold, Øyvind
Abstract: Background: The number of older adults with cancer is increasing. Radiotherapy is an important treatment modality for cancer and may cause side effects and distress. Patient-reported experience measures aim to measure patients' experiences with health care. This can help healthcare services to improve in line with patients' needs. To assess how Norwegian patients receiving radiotherapy experience their care, a valid and reliable tool is required. We selected the person-centred coordinated care experience questionnaire as a tool. Objective: The aim of the study is to validate the Norwegian version of the person-centred coordinated care experience questionnaire in a radiotherapy setting. Methods: A feasibility study of the person-centred coordinated care experience questionnaire and a cross-sectional study—testing psychometric properties of the questionnaire in a Norwegian radiotherapy setting—were conducted. Participants were recruited from two different hospitals in Norway. Patient characteristics and item scores are described using descriptive statistics. We performed an exploratory factor analysis and applied principal component analysis with a varimax rotation. Cronbach's α was used to assess internal consistency. Results: In total, 24 patients participated in the feasibility test, and 176 were included in the cross-sectional study where we explored the psychometric properties of the person-centred coordinated care experience questionnaire. Three factors were identified. Internal consistency was established for the 10-item scale, with Cronbach's α  = 0.698. Conclusions: Conclusions must consider the Norwegian setting and healthcare context. We found that the Norwegian version of the person-centred coordinated care experience questionnaire is a relevant, valid and reliable tool to provide insight into different areas of patients' experiences upon receiving radiotherapy. However, further testing on a larger sample is necessitated.